Composite sheet, inner container, cooking utensil and manufacturing method of composite sheet
By forming a coating with a columnar nanocrystal structure on the surface of stainless steel cooking utensils through physical vapor deposition, the problem of adsorbed stains on the surface of stainless steel being difficult to clean is solved, and the effects of high hardness, high non-stickness and easy cleaning are achieved.
Patent Information
- Application Number
- CN202310889542.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-18
- Publication Date
- 2025-01-21
AI Technical Summary
The surface of stainless steel cooking utensils is easy to absorb oil stains, dust and fingerprints, which is difficult to clean and affects beauty and hygiene.
A coating with a columnar nanocrystal structure is formed on the metal substrate through physical vapor deposition, including the surface layer, transition layer and bottom layer, to improve surface hardness, adhesion, non-stickiness and easy cleaning.
It achieves high surface hardness, high adhesion, high non-stickiness and easy cleaning, improving the service life and hygienic conditions of cooking utensils.
Smart Images

Figure CN119332205A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of cooking utensils, and in particular to a composite sheet, an inner pot, a cooking utensil and a method for manufacturing the composite sheet. Background Art
[0002] With the improvement of people's living standards and the demand for quality life, stainless steel products have been widely used in home furnishings, tableware, kitchen utensils and other fields. However, due to the high surface energy of stainless steel, it is easy to absorb stains such as oil, dust and fingerprints, which is difficult to clean, affecting the appearance and hygiene.
[0003] In order to solve this problem, people have developed some methods, such as chemical treatment on the surface of stainless steel, coating with special coatings, etc. However, these methods have some problems to a greater or lesser extent, such as the easy generation of pollution during the chemical treatment of the stainless steel surface, and the easy falling off of the non-stick coating or ceramic coating coated on the stainless steel surface.
[0004] Therefore, a composite sheet, an inner pot, a cooking utensil and a method for manufacturing the composite sheet are needed to at least partially solve the above problems. Summary of the invention
[0005] A series of simplified concepts are introduced in the Summary of the Invention section, which will be further described in detail in the Detailed Description of the Invention section. The Summary of the Invention section of this application does not mean to attempt to define the key features and essential technical features of the claimed technical solution, nor does it mean to attempt to determine the scope of protection of the claimed technical solution.
[0006] In order to at least partially solve the above problems, the first aspect of the present application provides a composite sheet, comprising:
[0007] Metal substrate;
[0008] The coating is attached to the surface of the metal substrate by physical vapor deposition, wherein the coating comprises a surface layer, and the surface layer is constructed as a columnar nanocrystal structure layer grown by physical vapor deposition.
[0009] According to the composite sheet of the present application, a coating having a columnar nanocrystal surface structure is formed on a metal substrate by physical vapor deposition, which can simultaneously obtain high surface hardness, high adhesion, high non-stickiness and high ease of cleaning.
[0010] Optionally, the coating further comprises a transition layer, the surface layer is attached to the transition layer, the transition layer comprises a first transition layer and a second transition layer, and the first transition layer and the second transition layer are alternately stacked. According to the above arrangement, the growth of the surface layer on the transition layer can improve the compactness of the surface layer, thereby improving the hardness and corrosion resistance.
[0011] Optionally, the coating further comprises a bottom layer, the bottom layer is attached to the metal substrate, and the bottom layer is a metal layer. According to the above configuration, the metal bottom layer can increase the bonding force between the coating and the metal substrate, making the coating less likely to fall off from the metal substrate, thereby increasing the service life.
[0012] Optionally, the surface layer is a titanium carbonitride layer, a chromium carbonitride layer or a zirconium carbonitride layer. According to the above configuration, the specific surface layer material can enable the surface layer to grow into a columnar nanocrystalline structure, further improving the non-stickiness and easy-to-clean properties of the composite sheet.
[0013] Optionally, the first transition layer is one of a titanium carbonitride layer, a chromium carbonitride layer and a zirconium carbonitride layer;
[0014] The second transition layer is one of a titanium carbonitride layer, a chromium carbonitride layer and a zirconium carbonitride layer;
[0015] The second transition layer is different from the first transition layer. According to the above configuration, the transition layer formed by alternating two material layers formed by titanium, chromium and zirconium base and their compounds can produce a template effect on the growth of the columnar nanocrystalline structure, causing lattice distortion, inhibiting the growth of coarse columnar nanocrystals on the surface, and making the columnar grains tend to grow vertically to the crystal plane, thereby reducing the surface energy of the surface layer, forming a small and dense columnar nanocrystalline structure, so that the composite sheet has good non-stickiness and easy cleaning properties, and as the surface layer becomes denser, its hardness and corrosion resistance are also improved.
[0016] Optionally, the bottom layer is a titanium metal layer, a chromium metal layer, a zirconium metal layer, a chromium-titanium composite metal layer, a chromium-zirconium composite metal layer or a zirconium-titanium composite metal layer. According to the above configuration, the metal bottom layer can increase the bonding force between the coating and the metal substrate, making it difficult for the coating to fall off from the metal substrate, thereby increasing the service life.
[0017] Optionally, the columnar nanocrystalline structure in the surface layer has a plurality of crystal grains growing in a columnar shape, the side surfaces of the plurality of crystal grains are bonded to each other, and when the surface layer is at a predetermined thickness, the top ends of the crystal grains grow to form protrusions, so that the surface structure of the surface layer is a nano-scale concave-convex structure. According to this solution, the surface of the coating forms a nano-scale concave-convex structure, which improves the non-stickiness and easy cleaning properties.
[0018] Optionally, the radial size of the grains is 20-80 nm; and / or
[0019] The predetermined thickness of the surface layer is 100-600 nm. According to this solution, a nanometer scale can be provided for the surface of the coating to form a special columnar nano crystal structure.
[0020] Optionally, the surface roughness of the metal substrate is 0.1-1.6 μm.
[0021] Optionally, the total number of the first transition layer and the second transition layer is 5-200 layers.
[0022] Optionally, the thickness of the bottom layer is 100-500 nm; and / or
[0023] The thickness of the transition layer is 300-1000 nm; and / or
[0024] The total thickness of the coating is 700-2000nm.
[0025] Optionally, the surface layer is a titanium carbonitride-copper composite layer, a chromium carbonitride-copper composite layer or a zirconium carbonitride-copper composite layer. According to the above configuration, adding copper to the surface layer can further reduce the surface energy of the surface layer and further improve the hydrophobicity and non-stickiness.
[0026] Optionally, amorphous copper is coated outside the grains of the columnar nanocrystalline structure. According to the above arrangement, since copper does not react with elements such as carbon and nitrogen, and cannot form a solid solution with carbonitrides, it exists in an amorphous form, thereby forming a structure in which copper is coated outside the grains. Such a structural form can further inhibit the growth of grains, form a finer grain structure, and effectively reduce the surface energy.
[0027] Optionally, the surface layer and the first transition layer or the second transition layer in contact with the surface layer in the transition layer contain the same carbonitride. According to the above configuration, the bonding force between the surface layer and the transition layer can be improved.
[0028] Optionally, the first transition layer or the second transition layer in contact with the bottom layer in the bottom layer and the transition layer contains the same metal element. According to the above configuration, the bonding force between the transition layer and the bottom layer can be improved.
[0029] A second aspect of the present application provides an inner liner, which is made of the composite sheet material described in the first aspect.
[0030] The inner liner according to the present application is made of the composite sheet material described in the first aspect above, and therefore has a technical effect similar to that of the composite sheet material of the first aspect above.
[0031] A third aspect of the present application is a cooking utensil, comprising the inner pot described in the second aspect.
[0032] The cooking utensil according to the present application has the inner pot of the second aspect, and thus has a technical effect similar to that of the inner pot of the second aspect.
[0033] A fourth aspect of the present application provides a method for manufacturing a composite sheet, the method comprising:
[0034] A metal substrate preparation step, pre-treating the metal substrate and placing the metal substrate in a physical vapor deposition device;
[0035] The physical vapor deposition step is to deposit a coating on the surface of the metal substrate. The physical vapor deposition step includes a surface layer deposition step: the surface layer of the coating is grown into a columnar nano-crystal structure by physical vapor deposition.
[0036] According to the manufacturing method of the composite sheet of the present application, a coating film having a columnar nanocrystalline structure can be deposited on the surface of a metal substrate, and the coating film has high hardness, high adhesion, high non-stickiness and easy cleaning properties.
[0037] Optionally, a deposition furnace of the physical vapor deposition device is provided with a rotating frame, a first metal target and a second metal target different from the first metal target, wherein the first metal target and the second metal target are arranged at intervals around the rotation axis of the rotating frame, the metal elements of the first metal target and the second metal target are selected from titanium, chromium or zirconium, and the physical vapor deposition device further has a carbon source and a nitrogen source;
[0038] The step of preparing the metal substrate comprises: placing the metal substrate on the rotating frame and making the surface to be deposited of the metal substrate face away from the rotating axis;
[0039] The step of depositing the surface layer also includes: opening one of the first metal target and the second metal target, opening a carbon source and a nitrogen source, and depositing the surface layer on the surface to be deposited of the metal substrate, wherein the metal element of the first metal target or the second metal target reacts with the carbon source and the nitrogen source to form the surface layer. According to the above arrangement, a columnar nanocrystalline surface layer of carbonitride can be grown on the surface of the metal substrate by the PVD process.
[0040] Optionally, the physical vapor deposition step further includes a transition layer deposition step, the transition layer deposition step is located before the surface layer deposition step, and the transition layer deposition step includes: opening the first metal target and the second metal target, and alternately depositing a first transition layer and a second transition layer on the surface to be deposited of the metal substrate by rotation, wherein the metal element of the first metal target reacts with the carbon source and the nitrogen source to form the first transition layer, and the metal element of the second metal target reacts with the carbon source and the nitrogen source to form the second transition layer. According to the above process, the metal substrate is alternately covered by the coating material produced by the first metal target and the second metal target by rotation, so that the alternating first transition layer and the second transition layer can be efficiently formed.
[0041] Optionally, the physical vapor deposition step further includes a bottom layer deposition step, which is located before the transition layer deposition step, and the bottom layer deposition step includes: opening the first metal target and / or the second metal target, closing the nitrogen source and the carbon source, continuously introducing argon gas into the deposition furnace, and depositing a metal bottom layer on the surface to be deposited of the metal substrate. According to the above configuration, the metal bottom layer can be deposited using the same PVD equipment, and the metal bottom layer can increase the bonding force between the coating and the metal substrate, so that the coating is not easy to fall off from the metal substrate, thereby increasing the service life.
[0042] Optionally, the carbon source is acetylene gas, and the nitrogen source is nitrogen gas;
[0043] The step of depositing the surface layer also includes: setting the volume ratio of nitrogen to acetylene gas to 1:1.8 to 1:2.2, setting the temperature of the deposition furnace to 280-300°C, applying a bias voltage of 140-160V to the metal substrate during deposition, and depositing for 10-30 minutes to control the thickness of the surface layer to be 100-600nm. According to the above settings, a surface layer with a specific thickness can be obtained through specific process parameters, further improving the hardness, bonding strength and easy cleaning of the coating.
[0044] Optionally, the step of depositing the transition layer further includes: setting the temperature of the deposition furnace to 240-260° C., adjusting the volume ratio of nitrogen and acetylene gas to 1:1.8 to 1:2.2, applying a bias voltage of 140-160V to the metal substrate during deposition, and depositing for 20-60 minutes to control the thickness of the transition layer to be 300-1000nm. According to the above settings, the hardness, bonding strength and easy cleaning of the coating can be further improved through specific process parameters.
[0045] Optionally, the step of depositing the bottom layer further comprises: setting the temperature of the deposition furnace to 200-450° C., glow cleaning the metal substrate for 3-7 minutes before deposition, applying a bias voltage of 50-250V to the metal substrate during deposition, and depositing for 5-15 minutes to control the thickness of the bottom layer to be 100-500nm. According to the above settings, a bottom layer with specific parameters can be obtained through specific process parameters.
[0046] Optionally, the rotation speed of the rotating frame is set to 0.5-3 rpm. According to this solution, the thickness of the coating can be effectively controlled.
[0047] Optionally, the step of preparing the metal substrate further comprises: polishing and cleaning the metal substrate so that the surface to be deposited of the metal substrate has a roughness of 0.1-1.6 μm. According to the above configuration, the smoother metal substrate surface can make the coating surface also have smooth characteristics, which is conducive to improving hydrophobicity, non-stickiness and easy cleaning.
[0048] Optionally, the metal substrate is first roughly polished by a hemp wheel, then finely polished by a cloth wheel, and then sequentially subjected to ultrasonic cleaning, pure water cleaning and drying. According to the above arrangement, the desired roughness can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] The following drawings of the present application are used as a part of the present application for understanding the present application. The drawings show the embodiments of the present application and their descriptions, which are used to explain the principle of the present application.
[0050] In the attached figure:
[0051] Figure 1 is a schematic cross-sectional view of a composite sheet according to one embodiment of the present application;
[0052] Figure 2 A more detailed schematic cross-sectional structure diagram of a coating of a composite sheet according to an embodiment of the present application;
[0053] Figure 3a-3d It is a schematic diagram of the cross-sectional structure of the surface layer of the coating according to the present application at different growth thicknesses;
[0054] Figure 4 is a top cross-sectional schematic diagram of a physical vapor deposition device according to an embodiment of the present application;
[0055] Figure 5 is a side cross-sectional schematic diagram of a physical vapor deposition device according to an embodiment of the present application;
[0056] Figure 6 A simplified flow chart of a method for manufacturing a composite sheet according to an embodiment of the present application;
[0057] Figure 7 A more detailed schematic flow chart of a method for manufacturing a composite sheet according to an embodiment of the present application. DETAILED DESCRIPTION
[0058] In the following description, a large number of specific details are provided to provide a more thorough understanding of the present application. However, it is apparent to those skilled in the art that the present application can be implemented without one or more of these details. In other examples, in order to avoid confusion with the present application, some technical features well known in the art are not described.
[0059] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should also be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates the presence of the features, wholes, steps, operations, elements and / or components, but does not exclude the presence or addition of one or more other features, wholes, steps, operations, elements, components and / or combinations thereof.
[0060] Ordinal numbers such as "first" and "second" cited in this application are merely identifiers and do not have any other meaning, such as a specific order. Moreover, for example, the term "first component" itself does not imply the existence of a "second component", and the term "second component" itself does not imply the existence of a "first component". It should be noted that the terms "upper", "lower", "front", "back", "left", "right", "inner", "outer" and similar expressions used in this document are for illustrative purposes only and are not limiting.
[0061] Now, exemplary embodiments according to the present application will be described in more detail with reference to the accompanying drawings.
[0062] refer to Figure 1 and Figure 2 In the first aspect of the present application, there is provided a composite sheet material, which includes a metal substrate 110 and a coating 150. The metal substrate 110 may be, for example, stainless steel, titanium, titanium alloy, aluminum alloy or the like. The coating 150 is attached to the surface of the metal substrate 110 by physical vapor deposition, wherein the coating 150 includes a surface layer 120, and the surface layer 120 is constructed as a columnar nanocrystalline structure layer grown by physical vapor deposition. Optionally, the columnar nanocrystalline structure in the surface layer 120 has a plurality of crystal grains 121 growing in a columnar shape, the side surfaces of the plurality of crystal grains 121 are attached to each other, and the radial dimension D of the crystal grains 121 is 20-80 nm. According to this solution, a nanoscale dimension can be provided for the surface of the coating 150 to form a special columnar nanocrystalline structure.
[0063] According to the composite sheet of the present application, a coating film 150 having a columnar nanocrystal surface structure is formed on a metal substrate 110 by physical vapor deposition, which can simultaneously obtain high surface hardness, high adhesion, high non-stickiness and high cleanability.
[0064] The above-mentioned nanoscale refers to a scale ranging from 1 to 100 nm.
[0065] The specific structure of coating 150 is referenced Figure 2The coating 150 includes a bottom layer 140, a transition layer 130 and a surface layer 120. The bottom layer 140 is attached to the surface of the metal substrate 110 by physical vapor deposition, the transition layer 130 is attached to the surface of the bottom layer 140 by physical vapor deposition, and the surface layer 120 is attached to the surface of the transition layer 130 by physical vapor deposition. In addition, the above-mentioned grains 121 grow in a direction perpendicular to the surface of the transition layer 130.
[0066] The bottom layer 140 is a metal layer. Thus, the metal bottom layer 140 and the metal substrate 110 have a strong bonding force. Exemplarily, the bottom layer 140 can be a titanium metal layer, a chromium metal layer, a zirconium metal layer, a chromium-titanium composite metal layer, a chromium-zirconium composite metal layer or a zirconium-titanium composite metal layer. The thickness of the bottom layer 140 is set to 100-500nm.
[0067] The transition layer 130 includes a first transition layer 131 and a second transition layer 132, and the first transition layer 131 and the second transition layer 132 are alternately stacked. The first transition layer 131 and the second transition layer 132 can be selected from one of a titanium carbonitride layer, a chromium carbonitride layer and a zirconium carbonitride layer, but the second transition layer 132 needs to be different from the first transition layer 131. The total number of the first transition layer 131 and the second transition layer 132 is 5-200 layers. The thickness of each layer of the first transition layer 131 and the second transition layer 132 can be 10-50nm. The total thickness of the transition layer 130 is set to 300-1000nm.
[0068] The surface layer 120 may be a titanium carbonitride layer, a chromium carbonitride layer or a zirconium carbonitride layer. The specific material of the surface layer 120 and / or the thickness of the surface layer 120 can enable the surface layer 120 to grow into a columnar nanocrystalline structure, further improving the non-stickiness and easy-to-clean properties of the composite sheet. For example, the thickness of the surface layer 120 is preferably set to 100-600nm. When the thickness of the surface layer 120 is within the above-mentioned predetermined thickness range, a protrusion can grow on the top of the grain 121, so that the surface of the surface layer 120 forms a nano-scale concave-convex structure.
[0069] refer to Figure 3a-3d The cross-sectional morphology of the surface layer 120 at different growth thicknesses is shown. Figure 3a The cross-sectional morphology is shown when the thickness of the surface layer 120 is 50 nm. Figure 3b The cross-sectional morphology when the thickness of the surface layer 120 is 100 nm is shown. Figure 3c The cross-sectional morphology is shown when the thickness of the surface layer 120 is 400 nm. Figure 3dThe cross-sectional morphology when the thickness of the surface layer 120 is 600nm is shown. It can be seen from the figure that when the thickness of the surface layer 120 is 50nm, the top of the grain 121 cannot grow a protrusion 122, and the surface of the surface layer 120 forms a flat surface. As the deposition thickness of the surface layer 120 increases, when the thickness is greater than 100nm as shown in the figure, the top of the grain 121 gradually grows a protrusion 122, and the protrusion 122 becomes more obvious and fuller as the deposition thickness increases. However, when the deposition thickness of the surface layer 120 increases from 400nm to 600nm, the protrusion 122 at the top of the grain 121 tends to be flattened. It can be seen that when the deposition thickness of the surface layer 120 exceeds 600nm, if the protrusion 122 at the top of the grain 121 continues to be flat, the concave-convex structure will become less obvious.
[0070] In addition, the transition layer 130, which is an alternating arrangement of two material layers formed by titanium, chromium and zirconium base and their compounds, can produce a template effect on the growth of the columnar nanocrystalline structure of the surface layer 120, causing it to undergo lattice distortion, thereby inhibiting the growth of coarse columnar nanocrystals in the surface layer 120, and causing the columnar grains 121 to tend to grow perpendicular to the crystal plane, thereby reducing the surface energy of the surface layer 120 and forming a fine and dense columnar nanocrystalline structure, so that the composite sheet has good non-stickiness and easy cleaning properties, and as the density of the surface layer 120 increases, its hardness and corrosion resistance also increase.
[0071] As an optional embodiment, the total thickness of the coating 150 is 700-2000nm, preferably 800-1600nm. Further preferably, the total thickness of the coating 150 is 1100-1300nm. Referring to Table 1, the performance test of embodiments of different coating 150 thicknesses is shown. Among them, the experimental steps for the easy cleaning of rice are as follows: (1) Add rice and water according to the regulations according to the type and volume of different cooking utensils; (2) Turn on the power to cook, and keep warm for 10 minutes after cooking; (3) Invert the cooking utensil and observe whether all the rice falls off by gravity or gently shaking the inner pot; (4) After cleaning the cooking utensil, repeat the above experiment for a total of 5 times to check the easy cleaning of the cooking utensil. The residual rice is rated according to the average residual weight of the last 4 times. The evaluation standards for the ease of cleaning of rice are as follows: Level 1: Lightly shake the cooking utensil or without shaking, and all the rice can fall off the utensil; Level 2: Lightly shake the cooking utensil, and there is still rice stuck to the inner pot, and the weight of the rice is ≤50g; Level 3: Lightly shake the cooking utensil, and there is still rice stuck to the inner pot, and the weight of the rice is 50g<rice weight≤100g; Level 4: Lightly shake the cooking utensil, and there is still rice stuck to the inner pot, and the weight of the rice is>100g.
[0072] Table 1
[0073]
[0074]
[0075] Among them, the hardness of the coating 150 increases with the increase of the total thickness. The bonding force between the coating 150 and the metal substrate 110 first increases and then decreases with the thickness, especially after the total thickness is greater than 2000nm, the bonding force drops sharply. In order to further improve the bonding force between the metal substrate 110 and the coating 150, the surface roughness of the metal substrate 110 is set to 0.1-1.6μm. Preferably, the surface roughness of the metal substrate 110 is set to 0.1-0.8μm. More preferably, the surface roughness of the metal substrate 110 is set to 0.1-0.4μm. In addition, setting a relatively smooth roughness can also make the surface of the coating 150 also have a smooth property, which is conducive to improving hydrophobicity, non-stickiness and easy cleaning.
[0076] For example, as a first optional embodiment, the surface layer 120 is a titanium carbonitride layer, the first transition layer 131 and the second transition layer 132 are respectively a titanium carbonitride layer and a chromium carbonitride layer, and the bottom layer 140 is a chromium-titanium composite metal layer. As a second optional embodiment, the surface layer 120 is a zirconium carbonitride layer, the first transition layer 131 and the second transition layer 132 are respectively a zirconium carbonitride layer and a chromium carbonitride layer, and the bottom layer 140 is a chromium-zirconium composite metal layer. As a third optional embodiment, the surface layer 120 is a chromium carbonitride layer, the first transition layer 131 and the second transition layer 132 are respectively a zirconium carbonitride layer and a titanium carbonitride layer, and the bottom layer 140 is a titanium-zirconium composite metal layer.
[0077] In order to further improve the bonding force between the surface layer 120 and the transition layer 130, the surface layer 120 and the first transition layer 131 or the second transition layer 132 in the transition layer 130 that contacts the surface layer 120 contain the same carbon nitride compound, for example, refer to the first optional embodiment and the second optional embodiment described above. In order to further improve the bonding force between the transition layer 130 and the bottom layer 140, the bottom layer 140 and the first transition layer 131 or the second transition layer 132 in the transition layer 130 that contacts the bottom layer 140 contain the same metal element, for example, refer to the first optional embodiment and the third optional embodiment described above.
[0078] In addition, copper can be added to the surface layer 120 to further improve the non-stick performance. That is, the surface layer 120 is a titanium carbonitride-copper composite layer, a chromium carbonitride-copper composite layer or a zirconium carbonitride-copper composite layer. Since copper does not react with elements such as carbon and nitrogen, and cannot form a solid solution with carbonitrides, the copper added to the carbonitrides will exist in an amorphous form, thereby forming a structure in which amorphous copper is coated outside the grains 121 of the columnar nanocrystalline structure. Such a structural form can further inhibit the growth of the grains 121, can form a finer grain structure, and effectively reduce the surface energy.
[0079] In this case, the optional combination of each layer can be: as a fourth optional embodiment, the surface layer 120 adopts a titanium carbonitride-copper composite layer, the first transition layer 131 and the second transition layer 132 are selected from a titanium carbonitride layer and a chromium carbonitride layer, respectively, and the bottom layer 140 adopts a chromium-titanium composite metal layer. As a fifth optional embodiment, the surface layer 120 adopts a chromium carbonitride-copper composite layer, the first transition layer 131 and the second transition layer 132 are selected from a titanium carbonitride layer and a chromium carbonitride layer, respectively, and the bottom layer 140 adopts a chromium-titanium composite metal layer. As a sixth optional embodiment, the surface layer 120 adopts a zirconium carbonitride-copper composite layer, the first transition layer 131 and the second transition layer 132 are selected from a zirconium carbonitride layer and a chromium carbonitride layer, respectively, and the bottom layer 140 adopts a chromium-zirconium composite metal layer. As a seventh optional embodiment, the surface layer 120 adopts a chromium carbonitride-copper composite layer, the first transition layer 131 and the second transition layer 132 are selected from a zirconium carbonitride layer and a titanium carbonitride layer, respectively, and the bottom layer 140 adopts a titanium-zirconium composite metal layer.
[0080] The second aspect of the present application provides an inner liner, which is made of the composite sheet material of the first aspect. The inner surface of the inner liner is provided with the above-mentioned coating 150, so that the surface layer 120 of the coating 150 faces inward. Optionally, the outer surface of the inner liner can also be provided with the above-mentioned coating 150, and the surface layer 120 of the coating 150 faces outward. According to the inner liner of the present application, it is made of the composite sheet material of the first aspect, and therefore has a technical effect similar to that of the composite sheet material of the first aspect.
[0081] The third aspect of the present application is a cooking utensil, the cooking utensil comprising the inner pot of the second aspect. The cooking utensil according to the present application has the inner pot of the second aspect, and thus has a similar technical effect as the inner pot of the second aspect.
[0082] The fourth aspect of the present application provides a method for manufacturing a composite sheet, referring to Figure 6 and Figure 7 , the method for manufacturing the composite sheet comprises:
[0083] Prepare the metal substrate step S1: pre-treat the metal substrate 110 and place the metal substrate 110 in the physical vapor deposition equipment 10 .
[0084] Physical vapor deposition step S2: depositing the coating film 150 on the surface of the metal substrate 110. The physical vapor deposition step includes a surface layer deposition step S23: growing the surface layer 120 of the coating film 150 into a columnar nanocrystalline structure by physical vapor deposition.
[0085] According to the manufacturing method of the composite sheet of the present application, a coating film 150 having a columnar nanocrystalline structure can be deposited on the surface of the metal substrate 110 , and the coating film 150 has high hardness, high adhesion, high non-stickiness and easy cleaning properties.
[0086] Among them, reference Figure 4 and Figure 5 The deposition furnace 11 of the physical vapor deposition device 10 is provided with a rotating frame 12, a first metal target 13 and a second metal target 14, and the second metal target 14 is different from the first metal target 13. The first metal target 13 and the second metal target 14 are arranged at intervals around the rotation axis of the rotating frame 12, and the metal elements of the first metal target 13 and the second metal target 14 are selected from titanium, chromium or zirconium. For example, the first metal target 13 can be a titanium target, and the second metal target 14 can be a chromium target. The physical vapor deposition device 10 also has a carbon source and a nitrogen source, wherein the carbon source is acetylene gas and the nitrogen source is nitrogen gas.
[0087] The metal substrate preparation step S1 is specifically as follows:
[0088] The metal substrate 110 is polished and cleaned so that the surface to be deposited of the metal substrate 110 has a roughness of 0.1-1.6 μm, preferably 0.1-0.8 μm, and more preferably 0.1-0.4 μm. The metal substrate 110 may be firstly roughly polished by a hemp wheel, then finely polished by a cloth wheel, and then successively subjected to ultrasonic cleaning, pure water cleaning, and drying treatment.
[0089] The metal substrate 110 is placed on the rotating frame 12 so that the surface of the metal substrate 110 to be deposited faces away from the rotation axis.
[0090] The physical vapor deposition step S2 also includes a transition layer deposition step S22 and a bottom layer deposition step S21. The transition layer deposition step S22 is located before the surface layer deposition step S23, and the bottom layer deposition step S21 is located before the transition layer deposition step S22. In other words, in the physical vapor deposition step S2, the bottom layer 140 is deposited first, the transition layer 130 is deposited, and finally the surface layer 120 is deposited.
[0091] Specifically, the physical vapor deposition step S2 includes:
[0092] In the bottom layer deposition step S21, the first metal target 13 and / or the second metal target 14 are turned on, the nitrogen source and the carbon source are turned off, argon gas is continuously introduced into the deposition furnace 11, and the metal bottom layer 140 is deposited on the surface to be deposited of the metal substrate 110. This solution can use the same PVD equipment to deposit the metal bottom layer 140. More specifically, the bottom layer deposition step also includes: setting the temperature of the deposition furnace 11 to 200-450°C, glow cleaning the metal substrate for 3-7 minutes before deposition, applying a bias voltage of 50-250V to the metal substrate 110 during deposition, and depositing for 5-15 minutes to control the thickness of the bottom layer 140 to be 100-500nm.
[0093] In step S22 of depositing transition layers, the first metal target 13 and the second metal target 14 are opened, and the first transition layer 131 and the second transition layer 132 are alternately deposited on the surface to be deposited of the metal substrate 110 by rotation, wherein the metal elements of the first metal target 13 react with the carbon source and the nitrogen source to form the first transition layer 131, and the metal elements of the second metal target 14 react with the carbon source and the nitrogen source to form the second transition layer 132. According to the above process, the metal substrate 110 is alternately covered with the coating materials produced by the first metal target 13 and the second metal target 14 by rotation, so that the first transition layer 131 and the second transition layer 132 alternately stacked can be efficiently formed. More specifically, the step of depositing the transition layer also includes: setting the temperature of the deposition furnace 11 to 240-260°C, adjusting the volume ratio of nitrogen and acetylene gas to 1:1.8 to 1:2.2, applying a bias voltage of 140-160V to the metal substrate 110 during deposition, and depositing for 20-60 minutes to control the thickness of the transition layer 130 to be 300-1000nm.
[0094] The surface layer deposition step S23 opens one of the first metal target 13 and the second metal target 14, opens the carbon source and the nitrogen source, and deposits the surface layer 120 on the surface to be deposited of the metal substrate 110, wherein the metal element of the first metal target 13 or the second metal target 14 reacts with the carbon source and the nitrogen source to form the surface layer 120. More specifically, the surface layer deposition step also includes: setting the volume ratio of nitrogen and acetylene gas to 1:1.8 to 1:2.2, setting the temperature of the deposition furnace 11 to 280-300°C, applying a bias voltage of 140-160V to the metal substrate 110 during deposition, and depositing for 10-30min to control the thickness of the surface layer 120 to be 100-500nm.
[0095] In the physical vapor deposition step S2 , the rotation speed of the rotating frame 12 is set to 0.5-3 rpm to more effectively control the thickness of the coating film 150 and make the thickness distribution of the coating film 150 uniform.
[0096] The processes and steps described in all the above preferred embodiments are only examples. Unless adverse effects occur, various processing operations can be performed in a sequence different from the sequence of the above processes. The sequence of steps in the above processes can also be increased, merged or deleted according to actual needs.
[0097] Unless otherwise defined, the technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present application. The terms used herein are only for describing specific implementation purposes and are not intended to limit the present application. The features described herein in one embodiment may be applied to another embodiment individually or in combination with other features, unless the feature is not applicable or otherwise specified in the other embodiment.
[0098] The present application has been illustrated through the above-mentioned embodiments, but it should be understood that the above-mentioned embodiments are only for the purpose of example and explanation, and the present application is not limited to the above-mentioned embodiments. According to the teachings of the present application, more variations and modifications can be made, and these variations and modifications all fall within the scope of protection claimed by the present application.
Claims
1. A composite sheet, characterized in that: include: Metal substrate; The coating is attached to the surface of the metal substrate by physical vapor deposition, wherein the coating comprises a surface layer, and the surface layer is constructed as a columnar nanocrystal structure layer grown by physical vapor deposition.
2. The composite sheet according to claim 1, characterized in that: The coating further includes a transition layer, the surface layer is attached to the transition layer, the transition layer includes a first transition layer and a second transition layer, and the first transition layer and the second transition layer are alternately stacked.
3. The composite sheet according to claim 2, characterized in that: The coating film further comprises a bottom layer, the bottom layer is attached to the metal substrate, and the bottom layer is a metal layer.
4. The composite sheet according to claim 1, characterized in that: The surface layer is a titanium carbonitride layer, a chromium carbonitride layer or a zirconium carbonitride layer.
5. The composite sheet according to claim 2, characterized in that: The first transition layer is one of a titanium carbonitride layer, a chromium carbonitride layer and a zirconium carbonitride layer; The second transition layer is one of a titanium carbonitride layer, a chromium carbonitride layer and a zirconium carbonitride layer; The second transition layer is different from the first transition layer.
6. The composite sheet according to claim 3, characterized in that: The bottom layer is a titanium metal layer, a chromium metal layer, a zirconium metal layer, a chromium-titanium composite metal layer, a chromium-zirconium composite metal layer or a zirconium-titanium composite metal layer.
7. The composite sheet according to claim 1, characterized in that: The columnar nanocrystal structure in the surface layer has multiple grains growing in a columnar shape, and the side surfaces of the multiple grains are bonded to each other. When the surface layer is at a predetermined thickness, the top ends of the grains grow to form protrusions, so that the surface structure of the surface layer is a nano-scale concave-convex structure.
8. The composite sheet according to claim 7, characterized in that: The radial size of the grains is 20-80 nm; and / or The predetermined thickness of the surface layer is 100-600 nm.
9. The composite sheet according to claim 1, characterized in that: The surface roughness of the metal substrate is 0.1-1.6 μm.
10. The composite sheet according to claim 2, characterized in that: The total number of the first transition layer and the second transition layer is 5-200 layers.
11. The composite sheet according to claim 3, characterized in that: The thickness of the bottom layer is 100-500 nm; and / or The thickness of the transition layer is 300-1000 nm; and / or The total thickness of the coating is 700-2000nm.
12. The composite sheet according to any one of claims 1 to 11, characterized in that: The surface layer is a titanium carbonitride-copper composite layer, a chromium carbonitride-copper composite layer or a zirconium carbonitride-copper composite layer.
13. The composite sheet according to claim 12, characterized in that: Amorphous copper encapsulates the grains of the columnar nanocrystalline structure.
14. The composite sheet according to claim 2, characterized in that: The surface layer and the first transition layer or the second transition layer in contact with the surface layer contain the same carbonitride.
15. The composite sheet according to claim 3, characterized in that: The base layer and the first transition layer or the second transition layer in contact with the base layer contain the same metal element.
16. A liner, characterized in that: The inner liner is made of the composite sheet according to any one of claims 1-15.
17. A cooking utensil, characterized in that: The cooking utensil comprises the inner pot according to claim 16.
18. A method for manufacturing a composite sheet, characterized in that: The method for manufacturing the composite sheet comprises: A metal substrate preparation step, pre-treating the metal substrate and placing the metal substrate in a physical vapor deposition device; The physical vapor deposition step is to deposit a coating on the surface of the metal substrate. The physical vapor deposition step includes a surface layer deposition step: the surface layer of the coating is grown into a columnar nano-crystal structure by physical vapor deposition.
19. The method for manufacturing a composite sheet according to claim 18, characterized in that: The deposition furnace of the physical vapor deposition device is provided with a rotating frame, a first metal target and a second metal target different from the first metal target, wherein the first metal target and the second metal target are arranged at intervals around the rotation axis of the rotating frame, the metal elements of the first metal target and the second metal target are selected from titanium, chromium or zirconium, and the physical vapor deposition device further has a carbon source and a nitrogen source; The step of preparing the metal substrate comprises: placing the metal substrate on the rotating frame and making the surface to be deposited of the metal substrate face away from the rotating axis; The step of depositing the surface layer also includes: opening one of the first metal target and the second metal target, opening a carbon source and a nitrogen source, and depositing the surface layer on the surface to be deposited of the metal substrate, wherein the metal element of the first metal target or the second metal target reacts with the carbon source and the nitrogen source to form the surface layer.
20. The method for manufacturing a composite sheet according to claim 19, characterized in that: The physical vapor deposition step also includes a transition layer deposition step, which is located before the surface layer deposition step, and the transition layer deposition step includes: opening the first metal target and the second metal target, and alternately depositing the first transition layer and the second transition layer on the surface to be deposited of the metal substrate by rotation, wherein the metal elements of the first metal target react with the carbon source and the nitrogen source to form the first transition layer, and the metal elements of the second metal target react with the carbon source and the nitrogen source to form the second transition layer.
21. The method for manufacturing a composite sheet according to claim 20, characterized in that: The physical vapor deposition step also includes a bottom layer deposition step, which is located before the transition layer deposition step. The bottom layer deposition step includes: opening the first metal target and / or the second metal target, closing the nitrogen source and the carbon source, continuously introducing argon gas into the deposition furnace, and depositing a metal bottom layer on the surface to be deposited of the metal substrate.
22. The method for manufacturing a composite sheet according to claim 19, characterized in that: The carbon source is acetylene gas, and the nitrogen source is nitrogen gas; The step of depositing the surface layer also includes: setting the volume ratio of nitrogen and acetylene gas to 1:1.8 to 1:2.2, setting the temperature of the deposition furnace to 280-300°C, applying a bias voltage of 140-160V to the metal substrate during deposition, and depositing for 10-30 minutes to control the thickness of the surface layer to 100-600nm.
23. The method for manufacturing a composite sheet according to claim 20, characterized in that: The carbon source is acetylene gas, and the nitrogen source is nitrogen gas; The step of depositing the transition layer also includes: setting the temperature of the deposition furnace to 240-260°C, setting the volume ratio of nitrogen and acetylene gas to 1:1.8 to 1:2.2, applying a bias voltage of 140-160V to the metal substrate during deposition, and depositing for 20-60 minutes to control the thickness of the transition layer to 300-1000nm.
24. The method for manufacturing a composite sheet according to claim 21, characterized in that: The bottom layer deposition step also includes: setting the temperature of the deposition furnace to 200-450°C, glow cleaning the metal substrate for 3-7 minutes before deposition, applying a bias voltage of 50-250V to the metal substrate during deposition, and depositing for 5-15 minutes to control the thickness of the bottom layer to 100-500nm.
25. The method for manufacturing a composite sheet according to any one of claims 19 to 24, characterized in that: The rotation speed of the rotating frame is set to 0.5-3 rpm.
26. The method for manufacturing a composite sheet according to any one of claims 18 to 24, characterized in that: The step of preparing the metal substrate further includes: polishing and cleaning the metal substrate so that the surface to be deposited of the metal substrate has a roughness of 0.1-1.6 μm.
27. The method for manufacturing a composite sheet according to claim 26, characterized in that: The metal substrate is firstly roughly polished by a hemp wheel, then finely polished by a cloth wheel, and then successively subjected to ultrasonic cleaning, pure water cleaning and drying treatments.